High-thermal-conductivity wave-absorbing composite material with flexibility and preparation method thereof
By using silicone rubber as a matrix in the composite material, combining high thermal conductivity carbon-based microspheres, magnetic wave-absorbing nanoparticles and flexible heat-absorbing fibers, the problem of existing materials being difficult to meet the high thermal conductivity, strong wave-absorbing and good flexibility at the same time, and the efficient heat dissipation and electromagnetic radiation absorption capacity of the composite material are achieved.
Patent Information
- Application Number
- CN202411923853.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing materials are difficult to meet the requirements of high thermal conductivity, strong wave absorption and good flexibility at the same time, which limits their wide application in modern high-tech fields.
Silicone rubber is used as a flexible polymer matrix, combining the uniform dispersion of highly thermally conductive carbon-based microspheres and magnetic wave-absorbing nanoparticles, as well as the introduction of flexible thermally conductive wave-absorbing fibers, the effective combination of flexibility, high thermal conductivity and excellent wave-absorbing performance of composite materials is achieved.
It realizes the excellent heat dissipation performance and electromagnetic radiation absorption capacity of composite materials, and can quickly conduct heat generated by electronic equipment, reduce equipment temperature, improve equipment stability and service life, while protecting the surrounding environment from electromagnetic interference.
Smart Images

Figure CN119775776A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, in particular to a high-thermal-conductivity and wave-absorbing composite material with flexibility and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology, the integration level of electronic equipment is increasing, and the problems of electromagnetic radiation and heat accumulation generated during operation are becoming more and more prominent. In addition, electromagnetic interference will also affect the normal operation of the equipment itself, resulting in signal transmission errors, performance degradation and even system failures, causing adverse effects on other surrounding electronic equipment, seriously restricting the reliability and stability of electronic equipment.
[0003] However, existing absorbing materials often find it difficult to strike a balance between flexibility and high thermal conductivity. Traditional rigid absorbing materials are greatly limited in application scenarios that require bending, folding or complex shapes due to their lack of flexibility. Flexible materials have relatively poor thermal conductivity and are unable to conduct heat away quickly and effectively, causing heat to accumulate inside the material, which in turn affects the absorbing performance and the overall stability of the material. In addition, phase separation and agglomeration are prone to occur in the uniform dispersion of the high thermal conductivity phase and the absorbing phase in the composite material and the interface bonding between them and the matrix, which greatly reduces the overall performance of the composite material.
[0004] In summary, existing materials cannot simultaneously meet the requirements of high thermal conductivity, strong wave absorption and good flexibility, which limits their wide application in modern high-tech fields. Therefore, there is an urgent need to develop a new type of flexible high thermal conductivity and wave absorbing composite material to overcome the shortcomings of existing technologies and meet the growing application needs in multiple fields. Summary of the invention
[0005] The purpose of the present invention is to make up for the deficiencies of the prior art and provide a flexible high thermal conductivity and wave absorbing composite material and a preparation method thereof. The invention adopts silicone rubber as a flexible polymer matrix, combines the uniform dispersion of high thermal conductivity carbon-based microspheres and magnetic wave absorbing nanoparticles, and introduces flexible thermal conductive wave absorbing fibers to achieve an effective combination of the flexibility, high thermal conductivity and excellent wave absorbing performance of the composite material. This composite material not only has excellent heat dissipation performance, can quickly conduct the heat generated by electronic equipment, reduce the temperature of the equipment, and improve the stability and service life of the equipment, but also has a strong wave absorbing ability, can effectively absorb and shield electromagnetic radiation, and protect the surrounding environment.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: On the one hand, a flexible high thermal conductivity and wave absorbing composite material, the composite material is composed of a flexible polymer matrix, high thermal conductivity carbon-based microspheres, magnetic wave absorbing nanoparticles and flexible thermal conductive wave absorbing fibers, specifically:
[0007] The flexible polymer matrix uses silicone rubber material as the matrix, accounting for 30%-50% of the total mass of the composite material, and the flexible polymer matrix is uniformly dispersed with surface-modified high-thermal-conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles;
[0008] The high thermal conductivity carbon-based microspheres are graphene microspheres and carbon nanotube microspheres, accounting for 15%-25% of the total mass of the composite material;
[0009] The magnetic wave-absorbing nanoparticles account for 10%-20% of the total mass of the composite material;
[0010] The flexible heat-conducting and wave-absorbing fiber is composed of a coaxial structure, which includes a core layer, a middle layer and an outer layer. The core layer is a high-thermal-conductivity metal wire copper wire that transfers heat to both ends of the fiber. The middle layer is an absorbing material layer, which is made of silicon carbide and boron nitride. The outer layer is a flexible polymer sheath layer, including polyimide and polyester.
[0011] Furthermore, the volume fraction of the flexible heat-conducting and wave-absorbing fibers in the composite material is 5%-20%.
[0012] Furthermore, the surfaces of the high thermal conductivity carbon-based microspheres and the magnetic wave-absorbing nanoparticles are modified into a composite layer of siloxane and metal oxide, and the mass ratio of the high thermal conductivity carbon-based microspheres to the magnetic wave-absorbing nanoparticles is 3:1-1:3.
[0013] Furthermore, the magnetic wave-absorbing nanoparticles include ferrite nanoparticles and carbonyl iron powder nanoparticles.
[0014] On the other hand, a method for preparing a flexible high thermal conductivity and wave absorbing composite material is provided, wherein the specific steps of the preparation method are:
[0015] S100, surface modification of high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles: placing high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles in a mixed solution containing a silane coupling agent and a metal alkoxide for surface modification, controlling the modification reaction temperature at 40-60° C. and the reaction time at 3-6 hours to obtain surface-modified high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles;
[0016] S200, preparation of flexible heat-conductive absorbing fiber: using high thermal conductivity metal wire as core material to deposit absorbing material layer on its surface, the deposition temperature is controlled at 300-500°C, the pressure is 1-5kPa, the deposition rate is 0.1-0.5μm / min, the deposited absorbing material layer is dip-coated on the absorbing material layer and wrapped with a flexible polymer sheath layer, the concentration of the polymer solution is controlled to be 10%-30%, and the dipping time is 10-30 seconds;
[0017] S300, preparation of composite materials: uniformly dispersing the surface-modified high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles in the S100 in a special flexible polymer matrix solution, wherein the mass ratio of the high thermal conductivity carbon-based microspheres to the magnetic wave-absorbing nanoparticles is 3:1-1:3, and the dispersion process is coordinated by ultrasound and high-speed stirring, the ultrasound power is 300-500W, and the stirring speed is 1000-1500rpm;
[0018] S400, dispersing and mixing: adding the flexible heat-conductive and wave-absorbing fiber prepared in S200 to the dispersion system of S300 at a volume fraction of 5%-20%, and blending by a twin-screw extrusion process to obtain a blend, wherein the temperature of each zone of the twin-screw is set to 150-250° C., and the screw speed is 80-120 rpm;
[0019] S500, step-by-step curing: curing the blend according to a step-by-step curing process, wherein the step-by-step curing includes primary curing, vacuum degassing and secondary curing, to obtain a high thermal conductivity and wave absorbing composite material with flexibility.
[0020] Furthermore, in the mixed solution of the silane coupling agent and the metal alkoxide in S100, the mass ratio of the silane coupling agent to the metal alkoxide is 1:2-2:1.
[0021] Furthermore, when the ultrasound and high-speed stirring are used in synergistic treatment in S300, the ultrasound treatment is first performed for 10-20 minutes, and then the high-speed stirring is performed for 20-30 minutes, and the steps are performed alternately 2-3 times.
[0022] Furthermore, the S400 preliminary curing is pre-cured at 60-80° C. for 1-2 hours to preliminarily fix the high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles in the matrix.
[0023] Furthermore, the S400 vacuum degassing is performed between pre-curing and secondary curing, the vacuum degree reaches 0.01-0.1 Pa, and the degassing time is 30-60 minutes.
[0024] Furthermore, the S400 secondary curing is performed at 120-150° C. for 2-4 hours.
[0025] Compared with the prior art, the flexible high thermal conductivity and wave absorbing composite material and the preparation method thereof have the following beneficial effects:
[0026] 1. The flexible high thermal conductivity and absorbing composite material of the present invention has a special material combination and structural design. Its flexible polymer matrix and flexible thermal conductive absorbing fiber give the composite material good bendability and stretchability, and can adapt to various complex deformation requirements. In terms of high thermal conductivity, the high thermal conductivity carbon-based microspheres and the high thermal conductivity metal core layer in the flexible thermal conductive absorbing fiber cooperate with each other to build an efficient heat conduction network, which can quickly export heat and effectively reduce the internal temperature of the material to avoid performance degradation caused by heat accumulation. For absorbing performance, the magnetic absorbing nanoparticles and the absorbing material layer in the flexible thermal conductive absorbing fiber work together to efficiently absorb electromagnetic waves in a wider frequency band, reduce the impact of electromagnetic interference on the surrounding environment and equipment, and ensure the stable operation of electronic equipment.
[0027] 2. The composite material preparation method of the present invention adopts a step-by-step curing process combined with vacuum degassing treatment, which effectively solves the dispersion problem of high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles in a flexible polymer matrix and the interface bonding problem with the matrix. In the step-by-step curing process, pre-curing is first performed to initially fix the particles, then vacuum degassing is performed to remove bubbles, and finally secondary curing is performed to strengthen the bonding, so that the particles are evenly and stably dispersed in the matrix, avoiding agglomeration and phase separation, and ensuring the consistency and stability of the composite material performance.
[0028] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 The present invention is a flow chart of a method for preparing a flexible, highly thermally conductive, wave-absorbing composite material. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] A flexible high thermal conductivity and wave absorbing composite material, the composite material is composed of a flexible polymer matrix, high thermal conductivity carbon-based microspheres, magnetic wave absorbing nanoparticles and flexible thermal conductive wave absorbing fibers, specifically:
[0033] In terms of the flexible polymer matrix, the selected silicone rubber (accounting for 30%-50% of the total mass of the composite material) has a molecular chain structure that can expand and contract freely, effectively buffering external stress, allowing the composite material to withstand repeated stretching, extrusion and bending deformation without breaking or losing performance, providing a stable and elastic basic framework for the entire composite material.
[0034] High thermal conductivity carbon-based microspheres use graphene microspheres (accounting for 40%-60% of the total mass of high thermal conductivity carbon-based microspheres) and carbon nanotube microspheres (accounting for 40%-60% of the total mass of high thermal conductivity carbon-based microspheres), which together account for 15%-25% of the total mass of the composite material. Graphene microspheres can quickly conduct heat within the plane; carbon nanotube microspheres build an efficient three-dimensional heat conduction channel. The two work together to greatly improve the thermal conductivity of the composite material in all directions, evenly disperse and conduct the heat in a timely manner, and effectively reduce the risk of material performance degradation caused by local overheating.
[0035] The magnetic wave-absorbing nanoparticles include ferrite nanoparticles (accounting for 40%-60% of the total mass of the magnetic wave-absorbing nanoparticles) and carbonyl iron powder nanoparticles (accounting for 40%-60% of the total mass of the magnetic wave-absorbing nanoparticles), accounting for 10%-20% of the total mass of the composite material. Ferrite nanoparticles can effectively absorb electromagnetic waves in a specific frequency band and convert them into heat energy; carbonyl iron powder nanoparticles enhance the magnetic coupling effect on electromagnetic waves. The two cooperate with each other to broaden the absorption frequency band and absorption intensity of the composite material to electromagnetic waves, significantly reduce the reflection and transmission of electromagnetic waves, and effectively reduce the impact of electromagnetic interference on surrounding electronic equipment and systems.
[0036] The flexible heat-conducting absorbing fiber is composed of a coaxial structure, a core layer of copper wire, an intermediate layer of an absorbing material layer composed of silicon carbide (accounting for 40%-60% of the total mass of the absorbing material layer) and boron nitride (accounting for 40%-60% of the total mass of the absorbing material layer), and an outer layer of a flexible polymer sheath layer composed of polyimide (accounting for 40%-60% of the total mass of the flexible polymer sheath layer) or polyester (accounting for 40%-60% of the total mass of the flexible polymer sheath layer), with a volume fraction of 5%-20% in the composite material. The core copper wire serves as the main heat conduction path to quickly conduct heat to both ends of the fiber; the intermediate layer of absorbing material efficiently absorbs and converts electromagnetic waves in a specific frequency band; the outer flexible polymer sheath layer, while ensuring the flexibility of the fiber, isolates the external environment from erosion and damage to the internal structure, and promotes good bonding between the fiber and the flexible polymer matrix.
[0037] Embodiment 1
[0038] This embodiment will describe in detail the specific implementation process of a method for preparing a flexible high thermal conductivity and wave absorbing composite material, and control the content of different components therein to present different performance results.
[0039] Surface modification of S100, high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles: Graphene microspheres (accounting for 60% of the total mass of high thermal conductivity carbon-based microspheres) and carbon nanotube microspheres (accounting for 40%) as well as ferrite nanoparticles (accounting for 60% of the total mass of magnetic absorbing nanoparticles) and carbonyl iron powder nanoparticles (accounting for 40%) were placed in a mixed solution containing a silane coupling agent and a metal alkoxide (the mass ratio of the silane coupling agent to the metal alkoxide was 1:2) for surface modification. The modification reaction temperature was controlled at 40°C and the reaction time was 6 hours to obtain surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles.
[0040] S200. Preparation of flexible thermally conductive absorbing fiber: copper wire is used as the core material and an absorbing material layer is deposited on the surface (silicon carbide accounts for 60% of the total mass of the absorbing material layer, and boron nitride accounts for 40%). The deposition temperature is controlled at 300°C, the pressure is 5 kPa, and the deposition rate is 0.1 μm / min. A flexible polymer sheath layer is wrapped around the absorbing material layer by dip coating (polyimide accounts for 60% of the total mass of the flexible polymer sheath layer, and polyester accounts for 40%). The concentration of the polymer solution is controlled to be 10%, and the immersion time is 30 seconds.
[0041] S300. Preparation of composite materials: The surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles are uniformly dispersed in the silicone rubber matrix solution, wherein the mass ratio of the high thermal conductivity carbon-based microspheres to the magnetic absorbing nanoparticles is 3:1. The dispersion process adopts ultrasonic and high-speed stirring synergistic treatment, first ultrasonic treatment for 10 minutes, then high-speed stirring for 30 minutes, alternating for 3 times, the ultrasonic power is 300 W, and the stirring speed is 1500 rpm.
[0042] S400, dispersion and mixing: adding the prepared flexible heat-conductive and wave-absorbing fiber into the dispersion system at a volume fraction of 5%, and blending the mixture through a twin-screw extrusion process to obtain a blend, wherein the temperature of each zone of the twin-screw is set to 150° C., and the screw speed is 120 rpm.
[0043] S500, step-by-step curing: pre-curing the blend at 60°C for 2 hours to initially fix the high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles in the matrix, and then performing vacuum degassing between pre-curing and secondary curing, with a vacuum degree of 0.01 Pa and a degassing time of 60 minutes. Finally, secondary curing is performed at 120°C for 4 hours to obtain a flexible high thermal conductivity absorbing composite material.
[0044] Performance test results: When the tensile strain of the composite material reaches 30%, the comprehensive index of absorption and thermal conductivity decreases by 8%. After repeated folding 800 times, the width of the absorption band changes by 8% and the thermal conductivity is maintained at a high level. The thermal conductivity reaches 8W / (m·K), and the absorption rate in the 8-12GHz frequency band reaches more than 90%.
[0045] Embodiment 2
[0046] S100, surface modification of high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles: Graphene microspheres (accounting for 50% of the total mass of high thermal conductivity carbon-based microspheres), carbon nanotube microspheres (accounting for 50%), ferrite nanoparticles (accounting for 50% of the total mass of magnetic absorbing nanoparticles) and carbonyl iron powder nanoparticles (accounting for 50%) were placed in a mixed solution containing a silane coupling agent and a metal alkoxide (the mass ratio of the silane coupling agent to the metal alkoxide was 1.5:1.5) for surface modification. The modification reaction temperature was controlled at 50°C and the reaction time was 4.5 hours to obtain surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles.
[0047] S200. Preparation of flexible thermally conductive absorbing fiber: copper wire is used as the core material to deposit an absorbing material layer on its surface (silicon carbide accounts for 50% of the total mass of the absorbing material layer, and boron nitride accounts for 50%), the deposition temperature is controlled at 400°C, the pressure is 3kPa, and the deposition rate is 0.3μm / min. Then, a flexible polymer sheath layer is wrapped around the absorbing material layer by dip coating (polyimide accounts for 50% of the total mass of the flexible polymer sheath layer, and polyester accounts for 50%), the concentration of the polymer solution is controlled to be 20%, and the immersion time is 20 seconds.
[0048] S300. Preparation of composite materials: The surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles are uniformly dispersed in the silicone rubber matrix solution, wherein the mass ratio of the high thermal conductivity carbon-based microspheres to the magnetic absorbing nanoparticles is 2:1. The dispersion process adopts ultrasonic and high-speed stirring synergistic treatment, first ultrasonic treatment for 15 minutes, then high-speed stirring for 25 minutes, alternating for 2.5 times, the ultrasonic power is 400 W, and the stirring speed is 1200 rpm.
[0049] S400, dispersion and mixing: adding the prepared flexible heat-conductive wave-absorbing fiber into the dispersion system at a volume fraction of 12%, and blending the mixture through a twin-screw extrusion process to obtain a blend, wherein the temperature of each zone of the twin-screw is set to 200° C., and the screw speed is 100 rpm.
[0050] S500, step-by-step curing: pre-curing the blend at 70°C for 1.5 hours to initially fix the highly thermally conductive carbon-based microspheres and magnetic absorbing nanoparticles in the matrix, and then performing vacuum degassing between pre-curing and secondary curing, with a vacuum degree of 0.05 Pa and a degassing time of 45 minutes. Finally, secondary curing is performed at 135°C for 3 hours to obtain a flexible, highly thermally conductive, absorbing composite material.
[0051] Performance test results: When the tensile strain of the composite material reaches 30%, the comprehensive index of wave absorption and thermal conductivity decreases by 6%. After repeated folding 800 times, the width of the wave absorption band changes by 6% and the thermal conductivity is maintained at a high level. The thermal conductivity reaches 10W / (m·K), and the wave absorption rate in the 6-10GHz frequency band reaches more than 92%.
[0052] Embodiment 3
[0053] Surface modification of S100, high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles: Graphene microspheres (accounting for 40% of the total mass of high thermal conductivity carbon-based microspheres) and carbon nanotube microspheres (accounting for 60%) as well as ferrite nanoparticles (accounting for 40% of the total mass of magnetic absorbing nanoparticles) and carbonyl iron powder nanoparticles (accounting for 60%) were placed in a mixed solution containing a silane coupling agent and a metal alkoxide (the mass ratio of the silane coupling agent to the metal alkoxide is 2:1) for surface modification. The modification reaction temperature was controlled at 60°C and the reaction time was 3 hours to obtain surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles.
[0054] S200. Preparation of flexible thermally conductive absorbing fiber: copper wire is used as the core material, and an absorbing material layer is deposited on its surface (silicon carbide accounts for 40% of the total mass of the absorbing material layer, and boron nitride accounts for 60%). The deposition temperature is controlled at 500°C, the pressure is 1kPa, and the deposition rate is 0.5μm / min. Then, a flexible polymer sheath layer is wrapped around the absorbing material layer by dip coating (polyimide accounts for 40% of the total mass of the flexible polymer sheath layer, and polyester accounts for 60%). The concentration of the polymer solution is controlled to be 30%, and the dipping time is 10 seconds.
[0055] S300. Preparation of composite materials: The surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles are uniformly dispersed in the silicone rubber matrix solution, wherein the mass ratio of the high thermal conductivity carbon-based microspheres to the magnetic absorbing nanoparticles is 1:1. The dispersion process adopts ultrasonic and high-speed stirring synergistic treatment, first ultrasonic treatment for 20 minutes, then high-speed stirring for 20 minutes, alternating twice, the ultrasonic power is 500 W, and the stirring speed is 1000 rpm.
[0056] S400, dispersion and mixing:
[0057] The prepared flexible heat-conductive wave-absorbing fiber was added into the dispersion system at a volume fraction of 20%, and the mixture was blended by a twin-screw extrusion process to obtain a blend. The temperature of each zone of the twin-screw was set at 250° C., and the screw speed was 80 rpm.
[0058] S500, step-by-step curing: pre-curing the blend at 80°C for 1 hour to initially fix the high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles in the matrix, and then performing vacuum degassing between pre-curing and secondary curing, with a vacuum degree of 0.1 Pa and a degassing time of 30 minutes. Finally, secondary curing is performed at 150°C for 2 hours to obtain a flexible high thermal conductivity absorbing composite material.
[0059] Performance test results: When the tensile strain of the composite material reaches 30%, the comprehensive index of wave absorption and thermal conductivity decreases by 5%. After repeated folding 800 times, the width of the wave absorption band changes by 5% and the thermal conductivity is maintained at a high level. The thermal conductivity reaches 12W / (m·K), and the wave absorption rate in the 4-8GHz frequency band reaches more than 95%.
[0060] Embodiment 4
[0061] Surface modification of S100, high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles: Graphene microspheres (accounting for 45% of the total mass of high thermal conductivity carbon-based microspheres) and carbon nanotube microspheres (accounting for 55%) as well as ferrite nanoparticles (accounting for 45% of the total mass of magnetic absorbing nanoparticles) and carbonyl iron powder nanoparticles (accounting for 55%) were placed in a mixed solution containing a silane coupling agent and a metal alkoxide (the mass ratio of the silane coupling agent to the metal alkoxide was 1.8:1.2) for surface modification. The modification reaction temperature was controlled at 45°C and the reaction time was 5 hours to obtain surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles.
[0062] S200. Preparation of flexible thermally conductive absorbing fiber: copper wire is used as the core material to deposit an absorbing material layer on its surface (silicon carbide accounts for 45% of the total mass of the absorbing material layer, and boron nitride accounts for 55%), the deposition temperature is controlled at 350°C, the pressure is 4 kPa, and the deposition rate is 0.2 μm / min. Then, a flexible polymer sheath layer is wrapped around the absorbing material layer by dip coating (polyimide accounts for 45% of the total mass of the flexible polymer sheath layer, and polyester accounts for 55%), the concentration of the polymer solution is controlled to be 15%, and the immersion time is 15 seconds.
[0063] S300. Preparation of composite materials: The surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles are uniformly dispersed in the silicone rubber matrix solution, wherein the mass ratio of the high thermal conductivity carbon-based microspheres to the magnetic absorbing nanoparticles is 1.5:1. The dispersion process adopts ultrasonic and high-speed stirring synergistic treatment, first ultrasonic treatment for 18 minutes, then high-speed stirring for 22 minutes, alternating for 2.2 times, the ultrasonic power is 350 W, and the stirring speed is 1300 rpm.
[0064] S400, dispersion and mixing: adding the prepared flexible heat-conductive wave-absorbing fiber into the dispersion system at a volume fraction of 15%, and blending the mixture through a twin-screw extrusion process to obtain a blend, wherein the temperature of each zone of the twin-screw is set to 180° C., and the screw speed is 110 rpm.
[0065] S500, step-by-step curing: pre-cure the blend at 65°C for 1.8 hours to initially fix the highly thermally conductive carbon-based microspheres and magnetic absorbing nanoparticles in the matrix, then perform vacuum degassing between pre-curing and secondary curing, with a vacuum degree of 0.03 Pa and a degassing time of 50 minutes, and finally perform secondary curing at 130°C for 3.5 hours to obtain a flexible, highly thermally conductive, absorbing composite material.
[0066] Performance test results: When the tensile strain of the composite material reaches 30%, the comprehensive index of absorption and thermal conductivity decreases by 7%. After repeated folding 800 times, the width of the absorption band changes by 7% and the thermal conductivity is maintained at a high level. The thermal conductivity reaches 9W / (m·K), and the absorption rate in the 7-11GHz frequency band reaches more than 91%.
[0067] Embodiment 5
[0068] Surface modification of S100, high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles: Graphene microspheres (accounting for 55% of the total mass of high thermal conductivity carbon-based microspheres) and carbon nanotube microspheres (accounting for 45%) and ferrite nanoparticles (accounting for 55% of the total mass of magnetic absorbing nanoparticles) and carbonyl iron powder nanoparticles (accounting for 45%) were placed in a mixed solution containing a silane coupling agent and a metal alkoxide (the mass ratio of the silane coupling agent to the metal alkoxide was 1.2:1.8) for surface modification. The modification reaction temperature was controlled at 55°C and the reaction time was 4 hours to obtain surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles.
[0069] S200. Preparation of flexible thermally conductive absorbing fiber: copper wire is used as the core material to deposit an absorbing material layer on its surface (silicon carbide accounts for 55% of the total mass of the absorbing material layer, and boron nitride accounts for 45%), the deposition temperature is controlled at 450°C, the pressure is 2kPa, and the deposition rate is 0.4μm / min. Then, a flexible polymer sheath layer is wrapped around the absorbing material layer by dip coating (polyimide accounts for 55% of the total mass of the flexible polymer sheath layer, and polyester accounts for 45%), the concentration of the polymer solution is controlled to be 25%, and the immersion time is 25 seconds.
[0070] S300. Preparation of composite materials: The surface-modified high thermal conductivity carbon-based microspheres and magnetic absorbing nanoparticles are uniformly dispersed in the silicone rubber matrix solution, wherein the mass ratio of the high thermal conductivity carbon-based microspheres to the magnetic absorbing nanoparticles is 2.5:1. The dispersion process adopts ultrasonic and high-speed stirring synergistic treatment, first ultrasonic treatment for 12 minutes, then high-speed stirring for 28 minutes, alternating for 2.8 times, the ultrasonic power is 450W, and the stirring speed is 1100rpm.
[0071] S400, dispersion and mixing: adding the prepared flexible heat-conductive wave-absorbing fiber into the dispersion system at a volume fraction of 18%, and blending the mixture through a twin-screw extrusion process to obtain a blend, wherein the temperature of each zone of the twin-screw is set to 220° C., and the screw speed is 90 rpm.
[0072] S500, step-by-step curing: pre-cure the blend at 75°C for 1.2 hours to initially fix the highly thermally conductive carbon-based microspheres and magnetic absorbing nanoparticles in the matrix, then perform vacuum degassing between pre-curing and secondary curing, with a vacuum degree of 0.08 Pa and a degassing time of 40 minutes, and finally perform secondary curing at 140°C for 2.5 hours to obtain a flexible, highly thermally conductive, absorbing composite material.
[0073] Performance test results: When the tensile strain of the composite material reaches 30%, the comprehensive index of wave absorption and thermal conductivity decreases by 9%. After repeated folding 800 times, the width of the wave absorption band changes by 9% and the thermal conductivity is maintained at a high level. The thermal conductivity reaches 11W / (m·K), and the wave absorption rate in the 5-9GHz frequency band reaches more than 93%.
[0074] Comparative Example
[0075] This comparative example adopts a conventional preparation method, does not perform surface modification on the high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles, and does not use step-by-step curing and vacuum degassing treatment in the preparation process of the composite material.
[0076] Unmodified graphene microspheres and carbon nanotube microspheres as well as ferrite nanoparticles and carbonyl iron powder nanoparticles are simply mixed with a silicone rubber matrix, and flexible thermal conductive absorbing fibers made of copper wire as a core material, silicon carbide and boron nitride as absorbing material layers, and polyimide or polyester as a flexible polymer sheath are directly added to the mixed system. After ordinary stirring and mixing, the composite material is cured at 100°C for 6 hours.
[0077] Performance test results: When the tensile strain of the composite material reaches 20%, the comprehensive indicators of absorption and thermal conductivity drop by more than 20%. After repeated folding 500 times, the width of the absorption band changes by more than 20% and the thermal conductivity drops significantly. The thermal conductivity is only 5W / (m·K). The maximum absorption rate in the 8-12GHz band is only about 70%.
[0078] In summary, the performance test results of the high thermal conductivity and wave absorbing composite materials prepared in Example 1, Example 2, Example 3, Example 4, Example 5 and the comparative example are shown in the following table:
[0079]
[0080]
[0081] As shown in the table above, it can be clearly seen from the table data that each embodiment has its own characteristics in the performance of the flexible high thermal conductive absorbing composite material and is significantly better than the comparative example. In terms of tensile strain performance, when the tensile strain reaches 30%, the decrease in the comprehensive performance of absorbing and thermal conductivity of Examples 1-5 is controlled between 5% and 9%, while the decrease in the comparative example exceeds 20% when the tensile strain is only 20%, indicating that the preparation method of the present invention effectively improves the performance stability of the material during the deformation process.
[0082] As for the repeated folding performance, the width of the absorbing frequency band of the embodiment changes by 5%-9% after 800 foldings, while the width of the comparative example changes by more than 20% after 500 foldings, which highlights the advantages of the present invention in ensuring the flexibility of the material and the stability of absorbing waves. As for the thermal conductivity, the embodiments 1-5 can reach 8-12W / (m·K), which is much higher than 5W / (m·K) of the comparative example, indicating that the material combination and process of the present invention can significantly improve the thermal conductivity. As for the wave absorption rate, the embodiments can achieve a high wave absorption rate of more than 90% in their respective specific frequency bands, while the comparative example can only achieve about 70% in the same frequency band, which further confirms the excellent results of the present invention in wave absorption performance. In short, the preparation method and material design of the present invention successfully achieve a good combination of flexibility, high thermal conductivity and strong wave absorption, have significant innovation and practicality, and show great application potential in the field of related materials.
[0083] In summary, through the study of the above embodiments, it can be known that the method for preparing a flexible high thermal conductive wave absorbing composite material of the present invention has a high degree of flexibility and controllability. By adjusting the component ratio of high thermal conductive carbon-based microspheres, magnetic wave absorbing nanoparticles, and flexible thermal conductive wave absorbing fibers and key parameters in the preparation process, the performance of the composite material can be accurately controlled, which reflects the technological advancement of the present invention.
[0084] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and range of equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A high thermal conductivity and wave absorbing composite material with flexibility, characterized in that: The composite material is composed of a flexible polymer matrix, highly thermally conductive carbon-based microspheres, magnetic wave-absorbing nanoparticles, and flexible thermally conductive wave-absorbing fibers, specifically: The flexible polymer matrix uses silicone rubber material as the matrix, accounting for 30%-50% of the total mass of the composite material, and the flexible polymer matrix is uniformly dispersed with surface-modified high-thermal-conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles; The high thermal conductivity carbon-based microspheres are graphene microspheres and carbon nanotube microspheres, accounting for 15%-25% of the total mass of the composite material; The magnetic wave-absorbing nanoparticles account for 10%-20% of the total mass of the composite material; The flexible heat-conducting and wave-absorbing fiber is composed of a coaxial structure, which includes a core layer, a middle layer and an outer layer. The core layer is a high-thermal-conductivity metal wire copper wire that transfers heat to both ends of the fiber. The middle layer is an absorbing material layer, which is made of silicon carbide and boron nitride. The outer layer is a flexible polymer sheath layer, including polyimide and polyester.
2. The high thermal conductivity and wave absorbing composite material with flexibility according to claim 1, characterized in that: The volume fraction of the flexible heat-conducting and wave-absorbing fiber in the composite material is 5%-20%.
3. The high thermal conductivity and wave absorbing composite material with flexibility according to claim 1, characterized in that: The surfaces of the high thermal conductivity carbon-based microspheres and the magnetic wave-absorbing nanoparticles are modified into a composite layer of siloxane and metal oxide, and the mass ratio of the high thermal conductivity carbon-based microspheres to the magnetic wave-absorbing nanoparticles is 3:1-1:
3.
4. The high thermal conductivity and wave absorbing composite material with flexibility according to claim 1, characterized in that: The magnetic wave-absorbing nanoparticles include ferrite nanoparticles and carbonyl iron powder nanoparticles.
5. A method for preparing a flexible high thermal conductivity and wave absorbing composite material, applicable to a flexible high thermal conductivity and wave absorbing composite material according to any one of claims 1 to 4, characterized in that: The specific steps of the preparation method are: S100, surface modification of high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles: placing high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles in a mixed solution containing a silane coupling agent and a metal alkoxide for surface modification, controlling the modification reaction temperature at 40-60° C. and the reaction time at 3-6 hours to obtain surface-modified high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles; S200, preparation of flexible heat-conductive absorbing fiber: using high thermal conductivity metal wire as core material to deposit absorbing material layer on its surface, the deposition temperature is controlled at 300-500°C, the pressure is 1-5kPa, the deposition rate is 0.1-0.5μm / min, the deposited absorbing material layer is dip-coated on the absorbing material layer and wrapped with a flexible polymer sheath layer, the concentration of the polymer solution is controlled to be 10%-30%, and the dipping time is 10-30 seconds; S300, preparation of composite materials: uniformly dispersing the surface-modified high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles in the S100 in a special flexible polymer matrix solution, wherein the mass ratio of the high thermal conductivity carbon-based microspheres to the magnetic wave-absorbing nanoparticles is 3:1-1:3, and the dispersion process is coordinated by ultrasound and high-speed stirring, the ultrasound power is 300-500W, and the stirring speed is 1000-1500rpm; S400, dispersing and mixing: adding the flexible heat-conductive and wave-absorbing fiber prepared in S200 to the dispersion system of S300 at a volume fraction of 5%-20%, and blending by a twin-screw extrusion process to obtain a blend, wherein the temperature of each zone of the twin-screw is set to 150-250° C., and the screw speed is 80-120 rpm; S500, step-by-step curing: curing the blend according to a step-by-step curing process, wherein the step-by-step curing includes primary curing, vacuum degassing and secondary curing, to obtain a high thermal conductivity and wave absorbing composite material with flexibility.
6. The method for preparing a flexible high thermal conductivity and wave absorbing composite material according to claim 5, characterized in that: In the mixed solution of the silane coupling agent and the metal alkoxide in S100, the mass ratio of the silane coupling agent to the metal alkoxide is 1:2-2:
1.
7. The method for preparing a flexible high thermal conductivity and wave absorbing composite material according to claim 5, characterized in that: When the ultrasound and high-speed stirring are used in S300 for coordinated treatment, the ultrasound treatment is first performed for 10-20 minutes, and then the high-speed stirring is performed for 20-30 minutes, and the steps are performed alternately 2-3 times.
8. The method for preparing a flexible high thermal conductivity and wave absorbing composite material according to claim 5, characterized in that: The S400 is pre-cured at 60-80° C. for 1-2 hours to preliminarily fix the high thermal conductivity carbon-based microspheres and magnetic wave-absorbing nanoparticles in the matrix.
9. The method for preparing a flexible high thermal conductivity and wave absorbing composite material according to claim 5, characterized in that: The S400 vacuum degassing is performed between pre-curing and secondary curing, the vacuum degree reaches 0.01-0.1 Pa, and the degassing time is 30-60 minutes.
10. The method for preparing a flexible high thermal conductivity and wave absorbing composite material according to claim 5, characterized in that: The S400 secondary curing is performed at 120-150° C. for 2-4 hours.
Citation Information
Patent Citations
Preparation method of anti-static polyester material based on carbon nanotube
CN103013057A
Stealth material system and preparation method thereof
CN111572109A
Composite material gasket, preparation method and application thereof, and electronic device
CN114891353A
Nanofiber membrane with temperature response as well as preparation method and application of nanofiber membrane
CN115874353A
Electromagnetic wave absorbing sheet-form fibric material
JP1985050902A
Cited By
Broadband wave-absorbing packaging structure based on alternation of magnetic layers and dielectric layers and preparation method
CN120566094A